2015
DOI: 10.1111/bju.13023
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of systematic transrectal biopsy to transperineal magnetic resonance imaging/ultrasound‐fusion biopsy for the diagnosis of prostate cancer

Abstract: Objectives To compare targeted, transperineal magnetic resonance imaging (MRI)/ultrasound (US)‐fusion biopsy to systematic transrectal biopsy in patients with previous negative or first prostate biopsy and to evaluate the gain in diagnostic information with systematic biopsies in addition to targeted MRI/US‐fusion biopsies. Patients and Methods In all, 263 consecutive patients with suspicion of prostate cancer were investigated. All patients were evaluated by 3‐T multiparametric MRI (mpMRI) applying the Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 34 publications
4
54
1
1
Order By: Relevance
“…In a systematic review by Moore et al, cancer was detected in 30% of all targeted cores in a pooled analysis of 1252 targeted cores compared to 7% of all systematic TRUS-guided biopsy cores in a pooled analysis of 5441 systematic cores. 30 The 56.9% CDR performed by systematic biopsy in our study is relatively high compared to other recent series from the literature, such as 34% in Borkowetz et al 31 and 44.2% in the meta-analysis from Wu et al, 32 but comparable to others, such as 56.5% in Siddiqui et al 12 or 56.6% in Mozer et al; 14 however, the overall 39.2% CDR for csPCa achieved by systematic biopsy is comparable to most recently published studies, ranging from 26.2-36.8%. 11,12,14,32 Comparing biopsy-naive men with those after at least one previous negative biopsy, overall CDR and CDR for csPCa were higher in the biopsy-naive group vs. repeat biopsy (69.3 vs. 57.1% and 54 vs. 46.6%, respectively).…”
Section: No Cancer Gleason 6 Gleason 3 + 4 Gleason 4 + 3 Gleason 8 Glsupporting
confidence: 38%
“…In a systematic review by Moore et al, cancer was detected in 30% of all targeted cores in a pooled analysis of 1252 targeted cores compared to 7% of all systematic TRUS-guided biopsy cores in a pooled analysis of 5441 systematic cores. 30 The 56.9% CDR performed by systematic biopsy in our study is relatively high compared to other recent series from the literature, such as 34% in Borkowetz et al 31 and 44.2% in the meta-analysis from Wu et al, 32 but comparable to others, such as 56.5% in Siddiqui et al 12 or 56.6% in Mozer et al; 14 however, the overall 39.2% CDR for csPCa achieved by systematic biopsy is comparable to most recently published studies, ranging from 26.2-36.8%. 11,12,14,32 Comparing biopsy-naive men with those after at least one previous negative biopsy, overall CDR and CDR for csPCa were higher in the biopsy-naive group vs. repeat biopsy (69.3 vs. 57.1% and 54 vs. 46.6%, respectively).…”
Section: No Cancer Gleason 6 Gleason 3 + 4 Gleason 4 + 3 Gleason 8 Glsupporting
confidence: 38%
“…In a previous study, we showed that fusion PBx was associated with a higher detection rate of clinically significant PCa, but we concluded that, because a high proportion of further tumours with GS ≥7 were detected by systematic PBx, systematic PBx should still be performed in addition to targeted PBx [15].…”
Section: Discussionmentioning
confidence: 79%
“…In a previous study, we reported a detection rate of 10% in PI-RADS ≤2 lesions for GS ≥7 tumours in patients undergoing combination PBx [15]. In the present study, the high detection rate in lesions classified as PI-RADS ≤2 compared with the RP specimen could be the result of positive selection, as all investigated patients in the present cohort had proven PCa; however, most of these PI-RADS score ≤2 lesions were associated with another lesion classified as PI-RADS ≥3 harbouring PCa so that the probability of finding evidence of PCa in lesions with PI-RADS ≤2 was higher in the present cohort.…”
Section: Discussionmentioning
confidence: 87%
“…The PI-RADS scores were distributed as follows (for patients with multiple lesions, the highest PI-RADS is stated): 39 lesions (16%) PI-RADS 3; 126 lesions (50%) PI-RADS 4; 86 lesions (34%) PI-RADS 5. A median of 3 (IQR 3-4) biopsy cores were obtained by TB and the total number of biopsy cores added to 13 (median; IQR [13][14].…”
Section: Resultsmentioning
confidence: 99%
“…In order to create a standard of reporting for mpMRI, the 'Prostate Imaging Reporting and Data System' (PI-RADS) by the ' European Society of Urogenital Radiology' (ESUR) was established [11,12] . Studies stated that a PI-RADS-based CDR showed the likelihood of detecting cancer increases with higher PI-RADS scores, that is, 70-100% for PI-RADS 5 [13][14][15][16] . In patients meeting the PRIAS criteria for active surveillance, the PI-RADS score was a strong predictor for an upgrading or upstaging after radical prostatectomy [17] .…”
Section: Introductionmentioning
confidence: 99%